1995
DOI: 10.1200/jco.1995.13.7.1609
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel by 1-hour infusion: an active drug in metastatic non-small-cell lung cancer.

Abstract: Paclitaxel administered by 1-hour infusion is an active and well-tolerated new agent in the treatment of metastatic non-small-cell lung cancer. These results suggest that a paclitaxel dose of 200 mg/m2 is more effective than 135 mg/m2 and can produce responses in patients previously treated with cisplatin-based regimens. Incorporation into combination regimens is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(54 citation statements)
references
References 11 publications
0
54
0
Order By: Relevance
“…Modifying the infusion time seems to have an effect on the risk of having a reaction to some agents, but additional research is needed to clarify this issue 42,43,73,74 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying the infusion time seems to have an effect on the risk of having a reaction to some agents, but additional research is needed to clarify this issue 42,43,73,74 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hainsworth et al 43 noted no difference in activity between 1-day and 3-day paclitaxel schedules in which each dose was administered by 1-hour infusion.…”
Section: Skin Testingmentioning
confidence: 99%
“…Oldergeneration drugs such as etoposide, vindesine, epirubicin and cisplatin are active as single-agents in previously untreated NSCLC, but do not achieve response rates over 10% when used in second-line setting [5]. The activity of new cytotoxic drugs such as gemcitabine, vinorelbine and paclitaxel in second-line setting is not well defined [5][6][7][8][9][10][11][12]. Most promising experience in second-line chemotherapeutic treatment of NSCLC is with docetaxel, which in phase II studies showed favourable tumour responses ranged from 16 to 22% [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The normal function of the microtubule network is thus disrupted, resulting in abnormal mitotic processes. Early treatment regimens examining the effectiveness of paclitaxel in non-small cell lung cancer (NSCLC) showed response rates of 21 to 24% (3,4) and an improved one-year survival rate, approaching 40% of patients treated. Due to the initial success of this chemotherapy, several combination trials have been executed, or are in the process, in the hope of finding paclitaxel combinations with increased efficacy, including paclitaxel combined with cisplatin (5), paclitaxel with carboplatin (reviewed in 6) and paclitaxel with radiation therapy (7).…”
Section: Introductionmentioning
confidence: 99%